Comparative study between the manual technique and the transepithelial in the removal of the corneal epithelium in photorefractive keraectomy (PRK) in a reference hospital in the city of Cascavel/PR (Research, Society and Development, 2022)
Photorefractive keratectomy (PRK) is a laser refractive procedure increasingly used in the treatment of ametropia. Postoperative discomfort is still a major disadvantage after PRK and, therefore, analyzing which technique provides the least degree of pain is of great importance. In this context, the study compared, through the application of the Wong-Baker pain assessment scale, which technique, manual or transepithelial, to remove the corneal epithelium generated a lower degree of pain after the procedure. For this, 16 patients (32 eyes), 8 (16 eyes) submitted to the manual technique and 8 (16 eyes) submitted to the transepithelial technique, filled the pain scale selected in the immediate postoperative period, from the first to the fourth day. After verifying the data, which also took into account the use of pain medication (Tylex) in the 4 days, found a higher prevalence of pain in patients undergoing the manual technique compared to the transepithelial technique, as well as a greater use of pain medication in the technique manual.